Selective flotation separation of kyanite from zircon in beach placer using sodium oleate as collector - Wen Yu; Qizhi Li; Chaohan Liu; Meian Wang; Mingxing Cheng; Xinwei Li; Ting Liao; Jiangan Chen (Minerals Engineering, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

A crystallinity-switch strategy for in-situ encapsulating Pd nanoclusters toward selective conversion of CO2 - Zhao-Cheng Shi; Jing Li; Xue-Feng Zhang; Ming-Ming Wu; Zhonggao Zhou; Meng-Tian Zhang; Chun-Ting He (Chemical Engineering Journal, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Flotation separation of rutile and zircon in electrostatic separation middlings and its separation mechanism - Wen Yu; Xinwei Li; Mingxing Cheng; Jinlong Zhai; Ting Liao; Meian Wang; Jiangan Chen (Minerals Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

SNX8 interacts with THOC7 to negatively regulate IFN 1 response via the TBK1-IRF3 signaling axis in teleost fish - Miao-miao Li; Chu-xin Wu; Ji-huan Hu; Ting-ting Yu; Ze-yin Jiang; Hong-ying Zhang; Xun-hang Li; Cheng-yu Hu (Fish & Shellfish Immunology, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Quaternary ammonium compounds in paired indoor dust and human urine: suspect screening and exposure associations - Fangyi Li; Zhendong Yang; Tingyu Li; Jiayong Lao; Kenneth M.Y. Leung; Xueyu Cheng; Zhengzhe Wan; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Tetrahydroisoquinoline alkaloids from the fruits of Piper nigrum and their chemotaxonomic significance - Yan Li; Bin Chen; Wei-Cheng Hu; Fu Li; Ting Shen (Biochemical Systematics and Ecology, 2026)

Preparation of K2CO3-activated biochar from peanut shell and Chlorella for enhanced carbamazepine adsorption: Performance, mechanism, and reusability - Zhenzhen Li; Jiayu Wu; Ting Cheng; Liling Zhou; Yujia Yang (Journal of Environmental Management, 2026)

Submicron-scale mineral weathering and organo-mineral association in the rhizosphere of iron ore tailings - Zhen Li; Songlin Wu; Ting-Shan Chan; Cheng-Wei Kao; Jian Wang; Gordon Southam; Longbin Huang (Geochimica et Cosmochimica Acta, 2026)

Ultrasound-activated endoplasmic reticulum-targeting piezoelectric nanoagonist with auxiliary intrinsic efficacy reverses tumor immunosuppression via spatiotemporal ICD in ovarian cancer - Shuangshuang Cheng; Haojia Li; Yuwei Yao; Ting Zhou; Wan Shu; Jiarui Zhang; Tangansu Zhang; Guanglei Zhong; Guanxiao Chen; Xiaoyu Shen; Yingying Peng; Shuyang Yu; et al. (Chemical Engineering Journal, 2026)

Lithium-doped calcium silicate scaffolds induce miR-130a-rich M2 macrophage EV-accelerating diabetic bone healing through angiogenesis–osteogenic coupling and mitochondrial repair - Ting-You Kuo; Cheng-Yu Chen; Yen-Hong Lin; Der-Yang Cho; Tsung-Li Lin; Ming-You Shie (Chemical Engineering Journal, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Pore-fracture evolution and fractal characteristics of coal under triaxial compression: Insights from in-situ nuclear magnetic resonance - Hexiang Xu; Cheng Zhai; Pathegama G. Ranjith; Jizhao Xu; Hongda Wen; Ting Liu; Shuang Li; Bingyou Jiang; Bobo Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Triple oxygen isotope analysis of cave drip waters: insights into hydrological processes and paleoclimatic reconstruction - Lijuan Sha; Qisheng Liang; Yunxia Li; David Domínguez-Villar; Lijun Tian; Baoyun Zong; Yajie Yang; Jun-Yun Li; Haiwei Zhang; Ting-Yong Li; Hai Cheng (Geochimica et Cosmochimica Acta, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Ternary ZnO@ZIF@COF core-shell-shell heterostructures: Energy-band cascade and layered signal amplification for biogenic amine detection - Junxi Cheng; Ting Li; Chang Liu; Yichen Gong; Xuanjun Wang; Miaomiao Liu; Yueguang Li; Hewei Yang; Zihan Qin; Zhengyang Cheng; Liyuan Cai; Qihua Sun; et al. (Chemical Engineering Journal, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Seed priming with boron nanoparticles establishes Trans-Developmental defense to Restrict Cd translocation via cell wall remodeling in Ipomoea aquatica Forsk - Zhien Pu; Xin Qi; Jianyu Xie; Changlian Xu; Guiyin Wang; Shirong Zhang; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Bioresource Technology, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Innovative technologies and future perspectives in tumor microbiomics - Wan-Ting He; Xiaofang Xing; Fei Wang; Le Li; Ye Cheng; Gang Yao (Science China Life Sciences, 2026)

Reassessing the Neolithic chronology and cultural development at the Dadiwan Site - Zhiqi Pei; Jian Wang; Yuanxin Li; Changchun Liu; Yongbo Quan; Haiming Li; Yishi Yang; Ting Cheng; Mingjie Yi; Le Zhang; Hui Wang; Huan Xia; et al. (Science China Earth Sciences, 2026)

Regionalizing the vertically generalized production model (VGPM) for Sentinel-2 estimation of phytoplankton primary productivity in turbid inland waters - Ting Song; Yanjuan Xu; Hujun Zhang; Bingchuan Zhu; Ling Li; Dongyang Cheng; Ge Liu (Journal of Oceanology and Limnology, 2026)

The maternal gut microbiota influences myocardial maturation and diastolic function of offspring in mice - Shanshan Li; Yiqiong Zhang; Yang Li; Yuyang Lei; Hao Wu; Peining Liu; Wen Xi; Xiaozhen Zhuo; Pu Huang; Ting Yang; Ting Bai; Juanli Li; et al. (Science China Life Sciences, 2026)

Tumorigenesis of well-differentiated and dedifferentiated liposarcoma: 12q amplicon architecture, oncogenic cargo, and evolutionary progression - Aobo Zhuang; Xiao Zhou; Chengfei Xu; YangJu Chen; Xueling Wang; Runchun Li; Jiajing Hu; Yinxue Cheng; Yunyan Wan; Ting Wu; Wengang Li (Cancer and Metastasis Reviews, 2026)

LDLR family proteins: the REAL receptors for orthoflavivirus entry - Xiang Chen; Rui-Ting Li; Cheng-Feng Qin (Science Bulletin, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

A hybrid mantle source for Chang’E-5 basalt: insights from ultra-trace element ratios of olivine - Cheng-Yu Du; Shao-Bing Zhang; Hejiu Hui; Ting Liang; Wan-Cai Li; Yong-Fei Zheng (Geochimica et Cosmochimica Acta, 2026)

Natural hydrogels for active, intelligent and smart food packaging: Advances, challenges, and future perspectives - Siyu Cheng; Yu Wang; Ting Wang; Chuang Li; Dandan Li; Srinivas Janaswamy; Guangjun Nie (Food Packaging and Shelf Life, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Multitrophic predators shape and stabilize soil microbiome networks at a regional scale - Nan Jiang; Chunhui Liu; Huiping Ma; Yue Hu; Shi Cheng; Qijun Wu; Gen Li; Huixin Li; Ting Liu (Applied Soil Ecology, 2026)

Response of greenhouse gas emissions, nitrogen loss and microbial communities to the presence of conventional and biodegradable microplastics in soil - Wenxu Li; Mengxiao Li; Jiaju He; Zhenyu Huang; Jian Zeng; Christopher W.N. Anderson; Minghua Zhou; Cheng Zhang; Xuesong Gao; Di Zhao; Ting Lan (Applied Soil Ecology, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Seven undescribed metabolites from Ganoderma lucidum-derived endophytic Talaromyces sp. GLQ04 and their anti-DLBCL (diffuse large B-cell lymphoma) activities - Shan Liu; Hao Sun; Pei-Ting Li; Pei-Shan Li; Xia Cheng; Feng Wang; Qi Luo (Phytochemistry, 2026)

Disrupting the lepidolite structure via low-temperature (NH4)2SO4 and Na2SO4 roasting: Achieving efficient co-extraction of lithium, rubidium, and cesium from lepidolite - Shuping Cheng; Zhipeng Rao; Jiezhong Zou; Junfeng Zhang; Guobiao Li; Huiquan Li; Ting Lai; Wanhai Xiao; Yong Lin; Tinggang Li; Dong Wang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Phosphorylated chitosan in-situ ionic self-crosslinked sulfonated poly(etherether ketone) proton exchange membrane for direct methanol fuel cells” [Fuel 427(Part E) (2027) 140108] - Zhuo Li; Guoliang Liu; Fuqiang Hu; Ying Ou; Ting Qu; Yong Liu; Fan Cheng; Quanyuan Zhang; Zushun Xu; Hai Liu; Jie Wang (Fuel, 2026)

Multifunctional LiSCN modified SnO2 electron transport layer for efficient and stable n-i-p perovskite solar cells - Liang Lei; Song Zhang; Ting Zhu; Cheng Gao; Yafei Liu; Zhangbo Lu; Zhitao Shen; Ming Li; Dan Chi; Jianlong Kou; Shunchang Liu; Shihua Huang (Chemical Engineering Journal, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Efficient remediation of multi-PTE contaminated farmland by synergistic dissolution of soil metal oxides using wood vinegar and FeSO4 co-washing - Tianying LÜ; Xinlei JI; Xiaoxun XU; Guochun LÜ; Changlian XU; Guiyin WANG; Shirong ZHANG; Zhanbiao YANG; Zhang CHENG; Junzhuo CAI; Heng LÜ; Ting LI; et al. (Pedosphere, 2026)

Solid waste dumping differentially impacts soil prokaryotic, fungal, and viral communities: Insights from metagenomics - Rongzhou Jin; Can Chen; Jingru Zhang; Yanying Li; Ye Wu; Feifan Wang; Zhipeng Chen; Ting Huang; Qijie Cheng; Xinlin Yu; Pu Jia (Journal of Environmental Sciences, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

A high-performance LaSA-Co MAs catalyst derived implantable flexible electrochemical sensor for endogenous dopamine detection - Binqi He; Jiawei Li; Qianzuo Liu; Xinyue Xiang; Sifan Sun; Haoran Yang; Guosheng Cheng; Maiyong Zhu; Ying Hao; Ting Zhang; Tie Li (Chemical Engineering Journal, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Altered soil dominant N and P supply fractions mediate ANPP via plant nutrient uptake efficiency under alpine meadow degradation - Yiran Li; Xin Lu; Dagang Yuan; Shirong Zhang; Yulin Pu; Yuanjun Luo; Ting Li; Xiaoxun Xu; Yongxia Jia; Guiyin Wang; Ying Cheng (Journal of Environmental Management, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

The occupations of microblade technology populations at Jiangjunbu02 site on the northeastern Tibetan Plateau and their relationships with paleoenvironment changes - Yuanxin Li; Juanting Yao; Xuke Shen; Linxueyi Wang; Yan Zhou; Huan Xia; Dongpeng Lin; Lin Chen; Yongxiu Lu; Jian Wang; Ting Cheng; Yan Zhao; et al. (Science China Earth Sciences, 2026)

Enhancing the immunogenicity of a recombinant PEDV subunit vaccine: the role of lipoprotein signal peptide - Haroon Afzal; Muhammad Umar; Nguyen-Thanh Hoa; Guan-Ming Ke; Li-Ting Cheng (Archives of Virology, 2026)

Effects of Green Manuring on Soil Health Improvement and Cadmium Immobilization–a Review Based on Meta-analysis - Ting Liang; Danna Chang; Jiancheng Xie; Jinxin Sun; Cheng Cai; Xinyan Li; Weidong Cao (Current Pollution Reports, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ca-wood vinegar modified biochar from invasive plant Spartina alterniflora: the amelioration effect on coastal “saline-alkali soil-Pennisetum giganteum” - Mingping Sheng; Ting Tian; Zhihan Cheng; Shaoxin Zi; Peiwen Li; Wenyuan Zhu; Youwen Li; Hongyan Guo (Journal of Environmental Management, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

Developmental trajectories of reading and neural substrates: a lifespan perspective on Chinese reading - Qianting Cheng; Hengyu Mao; Xinyang Liu; Xitong Liang; Yongbin Wei; Ting Qi; Li Liu (Brain Structure and Function, 2026)

City-Facade: A city-level large-scale point cloud building facade dataset for semantic & instance segmentation - Yiping Chen; Jonathan Li; Ting Han; Huifang Feng; Jun Chen; Cheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Deciphering the microbial complexity of Chinese traditional sourdough through integrated learning - Yan Liu; Jinyu Wang; Shiwei Zhou; Feijiang Li; Honghong Cheng; Zheqing Zhu; Jiale Wang; Aowen Liu; Ting Lu; Yujuan Yu; Senmiao Tian; Min Zhang; et al. (Food Research International, 2026)

Optimizing soil microbial functions under long-term straw return enhances nutrient acquisition, thereby improving nutrient availability and crop productivity in tobacco–rice rotation systems of southern China - Bianhong Zhang; Rikun Li; Zhicheng Chen; Chunli Zeng; Songquan Liao; Yazhou Liu; Ting Cheng; Yifei Liu; Lina Tang; Wenxiong Lin; Jinwen Huang (Agriculture, Ecosystems & Environment, 2026)

Development of a Novel Experimental System for Simulating the Whole Grouting Process of Diffusion–Filling–Splitting in Deep Rock Engineering - Xia-Ting Feng; Xi-Fan Li; Yang-Yi Zhou; Cheng-Xiang Yang; Tian-Xiang Song (Rock Mechanics and Rock Engineering, 2026)

Soil aggregate carbon stocks and sequestration efficiency under long-term fertilization across China’s croplands - Man Cheng; Zhixuan Chen; Ting Shi; Haiyang Ma; Yongli Wen; Puwang Li; Minggang Xu (Soil and Tillage Research, 2026)

Mechanistic insights into gas capture and diffusion during the CO2 separation of mixed matrix membranes using ZIF materials as nanofillers - Han-chong Liu; Hong-li Chen; Li-guang Wu; Ting Wang; Hua-li Chen; Cheng Hu (Process Safety and Environmental Protection, 2026)

Single-grain luminescence dating of K-feldspar based on the pre-dose MET-pIRIR protocol - Ting Cheng; Bo Li; Dongju Zhang (Quaternary Geochronology, 2026)

A novel alginate-assisted immobilization strategy for enhanced biofilm development and nitrogen removal in membrane aerated biofilm reactors (MABRs) - Abdallah Abdelfattah; Reham Eltawab; Ke Li; Zhong-Ting Hu; Liang Cheng (Journal of Water Process Engineering, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

miR-124 Ameliorates Spatial Memory Deficits in Rats Exposed to Single-Prolonged Stress by Downregulating IQGAP1 to Regulate Actin-Binding Proteins and Apoptosis in Hippocampal Neurons - Qi An; Miao Li; Xin-Yu Ji; Cheng-Hao Piao; Shu-Ting Yang; Lei Tong; Li-Li Ji (Molecular Neurobiology, 2026)

Whole-Transcriptome Sequencing Identifies Key mRNAs, miRNAs, lncRNAs, and circRNAs of Sugar Beet in Response to Long Days - Naiguo Liang; Ting Wang; Li Zhao; Hedong Lu; Dayou Cheng (Journal of Plant Growth Regulation, 2026)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Correction: Sbmyb111 act as a transcriptional activator of flavonoid synthesis in Scutellaria baicalensis - Yao Xu; En Li; Weiping Cao; Yingchao Zhang; Xinfang Zhang; Zhaoyu Liu; Shanshan Cai; Jiayu Wang; Fansheng Cheng; Ruibing Chen; Ting Gao (Plant Molecular Biology, 2025)

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Structural engineering of flagellin as vaccine adjuvant: quest for the minimal domain of flagellin for TLR5 activation - Haroon Afzal; Asad Murtaza; Li-Ting Cheng (Molecular Biology Reports, 2025)
Flagellin stimulates Toll-like receptor 5 (TLR5), triggering both innate and adaptive immune responses, making it a potential vaccine adjuvant. On mucosal surfaces, flagellin induces a strong release of cytokines, chemokines, and immunoglobulins. When used in its free monomeric form, flagellin has been shown to enhance immune responses when combined with vaccine antigens. Further research demonstrated that genetically linking flagellin to the antigen provides a more consistent immune boost. However, the bulky structure of flagellin presents challenges in designing the antigen-adjuvant construct, leading to ongoing research to determine the minimal flagellin domain necessary for its adjuvant effect. Early findings suggest that only the D0 and D1 domains are required for immune enhancement. Functional analysis revealed that the TLR5-binding region is located in the D1 domain, while TLR5 dimerization and signaling require the presence of D0. Further reductions in the size of the D0 and D1 domains may be possible as deeper studies aim to identify the key residues responsible for TLR5 activation and immune enhancement. Additionally, flagellin is being tested as a hapten carrier alongside its established adjuvant role. Recently, significant advancements in flagellin application have been observed as it progresses through clinical studies as an adjuvant, anti-radiation, and anti-cancer agent.

NETs accelerate aortic valve calcification by promoting M1 macrophage polarization through the TLR9 signaling pathway - Luyao Liu; Zhenzhen Lan; Xincan Liu; Yun Chen; Zhihao Chen; Li Cheng; Ting Hu (Molecular and Cellular Biochemistry, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

Bioactive secondary metabolites from an endophytic fungus Chloridium virescens GLQ05 and structural revision of alteamide - Shan Liu; Pei-Ting Li; Peishan Li; Xinhuan Qiu; Xia Cheng; Qi Luo; Feng Wang (Natural Product Research, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Development and quality analysis of low GI composite buckwheat steamed bun - Ting Zhang; Jiayue Zhang; Wanzeng Li; Xinyuan Hu; Huiru Cheng; Kang An; Jingwen Wang; Dan Yang; Hua Li; Jun Xi; Kunlun Liu; Zhifeng Zhang; et al. (Journal of Cereal Science, 2025)

Modulating the redox states in a 3D conductive MOF for sweat ascorbic acid monitoring - Wei-Qi Wang; Han Xie; Feng Cheng; Ting Zou; Ke-Qiang Xu; Amare Aregahegn Dubale; Wen-Hui Zhang; Ning Xu; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Conserved domains of flagellin as adjuvants for an inactivated vaccine against porcine epidemic diarrhea virus - Haroon Afzal; Nguyen-Thanh Hoa; Asad Murtaza; Thu-Dung Doan; Yao-Chi Chung; Guan-Ming Ke; Li-Ting Cheng (The Veterinary Journal, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

The investigation of phosphonate-decorated covalent organic frameworks with photo responsive effect for the effective adsorption and separation towards rare earth elements - Runhan Yan; Hongmin Cui; Jingsong Shi; Wei Jiang; Fei Gao; Nanfu Yan; Yaqing Weng; Minghui Li; Yuewei Liu; Ting Cheng (Journal of Environmental Chemical Engineering, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Efficient removal of metals and resource recovery from acid mine drainage by modified chemical mineralization coupling sodium sulfide precipitation - Ting Li; Fange Cheng; Xin Du; Jianru Liang; Lixiang Zhou (Journal of Environmental Sciences, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

Spider-cavity structured Ag/PDA@NiCuO/CF evaporator with bilateral siphon-driven channels for enhanced solar desalination - Zijian Li; Long Cheng; Ziyi Wang; Mengya Chen; Liang Wang; Kuzmin Anton; Xingqiao Wu; Ting Bian (Chemical Engineering Journal, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

The PRIDE system: A photo-responsive platform for high-efficiency isolation of extracellular vesicles for Parkinson's disease diagnostics - Wenjing Zhang; Ting Zhang; Jiayu Ding; Jingwen Cao; Zheyan He; Yanling Liu; Yong Juan Zhao; Chungen Qian; Chenzhong Li; Jiasi Wang; Bo Peng; Cheng Jiang (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Pediatric Abdominal and Pelvic CT Scans and the Subsequent Risk of Malignancy and Benign Genital Tumors: A Retrospective Cohort Study - Feng-Yi Su; Chih-Feng Chen; Kevin Chih-Yang Huang; Cheng-Li Lin; Fuu-Jen Tsai; Jui-Ting Hsu; Shin-Lei Peng (Journal of Medical and Biological Engineering, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Dose-dependent molecular composition of dissolved organic matter in biochar-amended manure composts - Nennen Zhu; Ao Cheng; Xufang Yu; Xiaolong Liu; Ting Li; Xiujuan Zhou; Wenchao Ji; Xingjun Fan (Journal of Environmental Management, 2025)

Dinotefuran exposure induces immunotoxicity in zebrafish embryos - Yunshuo Cheng; Yacan Gong; Dan Li; Weiwei Feng; Yao Chen; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

Identifying Immune Response Protein Biomarkers in Parkinson’s-Related Cognitive Impairment and Depression - Qiaozhen Su; Ting Lu; Yan Xu; Zhe Li; Hongfeng Liang; Chunye Zheng; Kunhong Li; Linshuang Ye; Zhixuan Ren; Dafeng Hu; Yan Huang; Lihua Zhu; et al. (Molecular Neurobiology, 2025)

Empagliflozin Promotes Revascularization in Diabetic Mice Hindlimb Ischemia by Improving Vascular Endothelial Cell Function - Hanjie Liu; Yingfan Li; Xiaoqi Zhou; Ting Chen; Yuanyuan Liu; Shuai Hu; Cheng Wang; Qing Wang; Jianxiong Xu; Xiangyu Zhou; Yang Shen; Chaoping Yu; et al. (Cardiovascular Toxicology, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Biomass energy for a sustainable Taiwan: Technologies, policies, and future prospects - Yu-Wei Lin; Yu-Ting Liu; Li-Cheng Huang; Shing-Chou Lin; Shean-Jen Chen; YongMan Choi (Biomass and Bioenergy, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

Sbmyb111 act as a transcriptional activator of flavonoid synthesis in Scutellaria baicalensis - Yao Xu; En Li; Weiping Cao; Yingchao Zhang; Xinfang Zhang; Zhaoyu Liu; Shanshan Cai; Jiayu Wang; Fansheng Cheng; Ruibing Chen; Ting Gao (Plant Molecular Biology, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Influence of biochar on DOM formation in chicken manure composting: spectral properties and molecular weight analysis - Xiaolong Liu; Nennen Zhu; Ao Cheng; Xiujuan Zhou; Dan Chen; Ting Li; Xufang Yu; Wenchao Ji; Xingjun Fan (Environment, Development and Sustainability, 2025)

Dracotangusions A and B, two new sesquiterpenes from Dracocephalum tanguticum Maxim. with anti-inflammatory activity - Ting-Ting Wang; Cheng-Peng Li; Yong-Sheng Wei; Zhao-Yue Dong; Fan-Cheng Meng; Min Chen; Xiao-Zhong Lan (Natural Product Research, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Endothelial GTPBP3 directs developmental angiogenesis and neovascularization after limb ischemia via the mtROS/HRl/ATF4/mTORC1 axis - Donglu Qin; Jiarui Hu; Yang Yang; Xin Li; Jia He; Jin Chen; Xin Guo; Cheng Wei; Fengjiao Wang; Ting Yi; Chenyu Li; Bilian Yu (Angiogenesis, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Designing flexible aliphatic linker based molecular imprinted covalent organic framework for rapid and selective extraction and detection of trace zearalenone - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Advanced materials for CO2 capture and storage: A comprehensive review of current progress and future prospects - Jun Wang; Linjin Li; Guangfei Qu; Minhua Cheng; Yuanchuan Ren; Ping Lu; Ting Zhang; Yaoze Wang; Fenghui Wu (Journal of Environmental Chemical Engineering, 2025)

Flower like ZnO hybrid mediated visible light harvesting film with upgraded photodynamic antibacterial capacity for effective food preservation - Qingqing Li; Xinjie Yang; Zhiyi Wu; Longdong Qin; Linpin Luo; Liang Zhang; Ting Du; Bingzhi Li; Yiyue Ma; Yuanyuan Cheng; Wenxin Zhu; Wentao Zhang; et al. (Food Chemistry, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Deep learning approach for reconstructing three-dimensional distribution of NO2 on an urban scale - Zhiguo Zhang; Qihua Li; Qihou Hu; Jingkai Xue; Ting Liu; Zhijian Tang; Fan Wang; Chengxin Zhang; Chuan Lu; Zhiman Wang; Meng Gao; Cheng Liu (Remote Sensing of Environment, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Down-regulation of platelet-derived growth factor receptor β in pericytes increases blood-brain barrier permeability and significantly enhances α-synuclein in a Parkinson’s Disease 3D cell model in vitro under hyperglycemic condition - Ting Wang; Meng-yan Li; Zhong Pei; Qiu-Xia Chen; Qiu-sheng Cheng; Ze Li (Tissue and Cell, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

The three-dimensional electrocatalytic oxidation system for refractory organic wastewater remediations: Mechanisms, electrode material and applications - Linjin Li; Yaoze Wang; Guangfei Qu; Ping Lu; Ting Zhang; Jun Wang; Minhua Cheng; Nanqi Ren; Yuanchuan Ren (Journal of Environmental Chemical Engineering, 2025)

Long-term spatiotemporal variations of ammonia in the Yangtze River Delta region of China and its driving factors - Jingkai Xue; Chengzhi Xing; Qihua Li; Shanshan Wang; Qihou Hu; Yizhi Zhu; Ting Liu; Chengxin Zhang; Cheng Liu (Journal of Environmental Sciences, 2025)

Application and comparative analysis of Enterococcus faecium CGMCC 29309 and Lactobacillus delbrueckii subsp. bulgaricus CGMCC 1.60194 in the preparation of fermented soymilk - Chang-Cheng Li; Zi-Yu Li; Yu-Ting Feng; Yu-Han Tian; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Network pharmacology-based strategy to reveal the mechanism of pinocembrin against ovarian cancer - Guanghui Wang; Jianxiang Cheng; Meizhen Yao; Jing Li; Ting Chen; Jia Zhang; Wensheng Du; Youguo Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Xiao-hong Li; Cheng Fu; Xue-ting Tan; Shi-jian Fu (Frontiers in Marine Science, 2025)
Introduction Fish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish ( Danio rerio ), and examines the persistence of these effects post-stressor removal. Methods Zebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors. Results Chronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated. Discussion Zebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

The Systematic Analysis of the Impact of China Water Improvement and Fluoride Reduction Project on Children - Bo Yang; Feiqing Wang; Xu Yang; Jinyang Cheng; Juan Chen; Bingbing Li; Ying Zhou; Xiaoxu Chen; Bo Wei; Xiaoshuang Yuan; Ting Tian; Dongxin Tang; et al. (Biological Trace Element Research, 2025)

Biochar enhanced co-composting for peat-free seedling substrate: A win-win solution for sustainable development of modern vegetable industry - Xiaoxia Fan; Yiyuan Wei; Dan Song; Ting Zhou; Ronghua Li; Xiaoxuan Su; Tao Zhang; Shang Cheng; Ran Xiao (Process Safety and Environmental Protection, 2025)

Evolution of the Asian summer monsoon during the Heinrich events 1–6 - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Jun-Yun Li; Hai Cheng; Chuan-Chou Shen; Jian Zhang; Ting-Yong Li (Global and Planetary Change, 2025)

Directional anchoring of polymer-lysozyme nanohybrids for adhesive capture and enhanced removal of Alicyclobacillus acidoterrestris in fruit juices - Bingzhi Li; Kun Cheng; Lunjie Huang; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Bangfeng Fu; Maojun Jin; et al. (Food Chemistry, 2025)

Corrigendum to “Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride” [Chem. Eng. J. 474 (2023) 145508] - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Unlocking dual-mode enzyme activities on bacterial surface: Directional recognition and swift capture of Alicyclobacillus acidoterrestris from fruit juices - Bingzhi Li; Kun Cheng; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Jing Sun; Maojun Jin; Jianlong Wang; et al. (Food Research International, 2025)

Effects of UV-A irradiation and microbial fermentation on the physicochemical, microstructure and functional properties of okara - Ya-Ting Lei; Fan-Bing Meng; Xiao-Lei Jiao; Yuan-Mou Tang; Qi-Jun Wu; Yun-Cheng Li (Food Research International, 2025)

Trace alkali-assisted exfoliation of silk fibers into liquid crystalline mesogens: Phase behaviors and structural manipulation - Yongfeng Wang; Qingqing Cheng; Yiyao Chen; Lianhui Li; Shuqi Wang; Mingming Hao; Pei-Xi Wang; Ting Zhang (Chemical Engineering Journal, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

Endophytic Bacteria Enterobacter cloacae PN7 Promotes Biosynthesis and Accumulation of Saponins in Panax notoginseng - Xianjing Lin; Mulan Wang; Feiyan Xie; Yuxi Cheng; Li Yang; Jian Gao; Weiqi Li; Xudong Zhang; Ting Tang (Current Microbiology, 2025)

Enhanced immune response with baculovirus-expressed BoHV-1 glycoprotein D in vaccine development - Nguyen-Thanh Hoa; Haroon Afzal; Uudamsaikhan Gundegmaa; Odbileg Raadan; Li-Ting Cheng; Chun-Yen Chu; Thu-Dung Doan; Yao-Chi Chung (The Veterinary Journal, 2024)

Revealing the characteristics of myxobacterial communities in rhizosphere and non-rhizosphere soils of halophytic plants following wetland degradation using high-throughput sequencing - Cheng Ding; Wenge Hu; Xiaoyun Qi; Suhui Hou; Yang Li; Jie Xiong; Ting Chen; Xue Zhang (Rhizosphere, 2024)

Calixarene incorporated molecular imprinting on covalent organic framework for supramolecular recognition and specific extraction of citrinin - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Ammonium mitigates cadmium toxicity by activating the bZIP20-APX2/CATA transcriptional module in rice seedlings in an ABA-dependent manner - Dong-Wei Di; Ting-Ting Li; Zheng-Lun Yu; Jie Cheng; Meng Wang; Chuan-Fa Liu; Yuan Wang; Herbert J. Kronzucker; Min Yu; Weiming Shi (Journal of Hazardous Materials, 2024)

Durable underwater superoleophobic hydrogels for oil- and Cu(II)-containing water purification - Chang-Lian Xu; Na Ji; Xingyue Wu; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Pietro Paolo de Oliveira e Silva; Guochun Lv; Junzhuo Cai; et al. (Journal of Environmental Chemical Engineering, 2024)

Closed-tube saltatory rolling circle amplification assay for rapid and visual detection of allergenic cashew nut in foods - Yingying Chen; Zipeng Guo; Zhaoqing Sun; Xinyu Wu; Yifan Xu; Zhengye Jin; Yuying Cheng; Zhen She; Qianqian Jiang; Yuxin Wo; Ting Wu; Hongwang Liu; et al. (Food Control, 2024)

Synergistic effects of selenium and zinc on Bletilla striata (Thunb.) Reichb. F. growth and polysaccharide antioxidation - Changli Hu; Chengying Wang; Yan Wu; Long Liang; Liwei Yin; Xu Cheng; Conghu Li; Ting Hu (BioMetals, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Ensuring China's food security in a geographical shift of its grain production: Driving factors, threats, and solutions - Shi Xue; Zhou Fang; Carena van Riper; Wei He; Xuxia Li; Fan Zhang; Ting Wang; Changgao Cheng; Qin Zhou; Zhongde Huang; Yang Bai (Resources, Conservation and Recycling, 2024)

Microscopic scale influence of functional groups on the displacement behavior of coalbed methane by hot humid flue gas: A molecular simulation study based on the dynamic injection process - Jing Huang; Cheng Zhai; Yong Sun; Yongshuai Lai; Hongyang Xu; Ting Huang; Yu Wang; Yujie Li; Jizhao Xu (Gas Science and Engineering, 2024)

Emulsions stabilized by okra polysaccharides: Physicochemical, interfacial, and emulsification properties - Yue Lv; Xiujuan Cai; Ting Xv; Hongxu Gao; Yuan Xv; Yuchao Gu; Dan Cheng; Mingyan Yan; Yinping Li (Food Hydrocolloids, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Metal-organic frameworks derived curled sheet-like Cu2O/CuO heterostructure: Low-power N2H4 sensing - Ting Li; Rui Gao; Xianfa Zhang; Xiaoli Cheng; Baosheng Li; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Recyclable UV shielding film with water vapor barrier and antimicrobial properties enabled by in situ polymerization of caffeic acid phenethyl ester - Yan Lyu; Jiongjiong Li; Fangmin Liang; Wencan Ma; Hongxia Liu; Cheng Huang; Jian Jiao; Ting Wu; Guigan Fang (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Natural insect-derived Nanoparticle: An ultra-bright and instantaneous Labeled signal tag for green and efficient Immunochromatographic assay of chloramphenicol - Shaochi Wang; Ting Du; Huilin Jia; Wentao Zhang; Jing Sun; Daohong Zhang; Zhenyu Li; Jie Cheng; Jianlong Wang (Chemical Engineering Journal, 2024)

A novel red fluorescent and dynamic nanocomposite hydrogel based on chitosan and alginate doped with inclusion complex of carbon dots - Yu Lan Tong; Kuan Yang; Wei Wei; Li Ting Gao; Peng Cheng Li; Xin Yi Zhao; Yong Mei Chen; Jianhui Li; Haopeng Li; Hideyuki Miyatake; Yoshihiro Ito (Carbohydrate Polymers, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Novel findings on the mitochondria in ciliates, with description of mitochondrial genomes of six representatives - Tengteng Zhang; Jinyu Fu; Chao Li; Ruitao Gong; Khaled A. S. Al-Rasheid; Naomi A. Stover; Chen Shao; Ting Cheng (Marine Life Science & Technology, 2024)
Determining and comparing mitochondrial genomes (mitogenomes) are essential for assessing the diversity and evolution of mitochondria. Ciliates are ancient and diverse unicellular eukaryotes, and thus are ideal models for elucidating the early evolution of mitochondria. Here, we report on six new mitogenomes of spirotrichs, a dominant ciliate group, and perform comparative analyses on 12 representative species. We show that: (1) the mitogenomes of spirotrichs are linear structures with high A+T contents (61.12–81.16%), bidirectional transcription, and extensive synteny (except for the nad5 , ccmf and cob genes in Euplotia); (2) the non-split of NADH dehydrogenase subunit 2 gene ( nad2 ) is a plesiomorphy of ciliates, whereas it has evolved into a split gene in Spirotrichea (apart from Euplotes taxa), Oligohymenophorea, and Armophorea; (3) the number of small subunit ribosomal proteins (rps) encoded in mitogenomes increases in the later branching classes of ciliates, whereas rps8 shows a loss trend during the evolution of Euplotes taxa; (4) the mitogenomes of spirotrichs exhibit A/T codon bias at the third position, and the codon bias is mainly due to DNA mutation in oligotrichs, hypotrichs and Diophrys appendiculata ; (5) the phylogenetic position of D. appendiculata is unstable and controversial based on both phylogenetic analyses and mitogenome evidence. In summary, we investigated the mitogenome diversity of spirotrichs and broadened our understanding of the evolution of mitochondria in ciliates.

Active longevity and aging: dissecting the impacts of physical and sedentary behaviors on longevity and age acceleration - Ting Yu Lu; Jiao Wang; Chao Qiang Jiang; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Wei Sen Zhang; Lin Xu (GeroScience, 2024)
Background To examine the associations of physical activity (PA) and sedentary behavior (SB) with longevity and age acceleration (AA) using observational and Mendelian randomization (MR) studies, and quantify the mediating effects of lipids. Methods In Guangzhou Biobank Cohort Study (GBCS), PA and SB were assessed by the Chinese Version of the International Physical Activity Questionnaire. Longevity was defined as participants whose age at follow-up or at death was at or above the 90th age percentile. AA was defined as the residual resulting from a linear model that regressed phenotypic age against chronological age. Linear regression and Poisson regression with robust error variance were used to assess the associations of total and specific PA in different intensities, and SB with AA and longevity, yielding βs or relative risks (RRs) and 95% confidence intervals (CIs). Two-sample MR was conducted to examine the causal effects. Mediation analysis was used to assess the mediating effects of lipids. Results Of 20,924 participants aged 50 + years in GBCS, during an average follow-up of 15.0 years, compared with low PA, moderate and high PA were associated with higher likelihood of longevity (RR (95% CI): 1.56 (1.16, 2.11), 1.66 (1.24, 2.21), respectively), and also cross-sectionally associated with lower AA (β (95% CI): -1.43 (-2.41, -0.45), -2.09 (-3.06, -1.11) years, respectively). Higher levels of moderate PA (MPA) were associated with higher likelihood of longevity and lower AA, whereas vigorous PA (VPA) showed opposite effects. The association of PA with longevity observed in GBCS was mediated by low-density lipoprotein cholesterol (LDL-C) by 8.23% (95% CI: 3.58–39.61%), while the association with AA was mediated through LDL-C, triglycerides and total cholesterol by 5.13% (3.94–7.30%), 7.81% (5.98–11.17%), and 3.37% (2.59–4.80%), respectively. Additionally, in two-sample MR, SB was positively associated with AA (β (95% CI): 1.02 (0.67, 1.36) years). Conclusions PA showed protective effects on longevity and AA, with the effects being partly mediated through lipids. Conversely, SB had a detrimental impact on AA. MPA was associated with higher likelihood of longevity and reduced AA, whereas VPA showed adverse effects. Our findings reinforce the recommendation of “sit less and move more” to promote healthy longevity, and highlight the potential risks associated with VPA in the elderly.

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Tuning the planarity of molecularly imprinted covalent organic frameworks for selective extraction of ochratoxin A in alcohol samples - Hao-Ze Li; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Food Chemistry, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

New therapeutic target NCF1-directed multi-bioactive conjugate therapies prevent preterm birth and adverse pregnancy outcomes - Juan Cheng; Xiaoyan Jia; Limei Yang; Siqi Zhang; Zhiyu Chen; Qian Gui; Ting Li; Zedan Pu; Hongbo Qi; Jianxiang Zhang (Science Bulletin, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Immunoprotective efficacy evaluation of OmpTS subunit vaccine against Aeromonas hydrophila infection in Megalobrama amblycephala - Zehua Xu; Minying Zhang; Ting Zhang; Hujun Cui; Hongping Li; Xu Wang; Xiaoheng Zhao; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Zhujin Ding (Fish & Shellfish Immunology, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Recycling alginate-like extracellular polymers (ALE) from municipal sludge: Value-added products and external impact - Ming Cheng; Chen Shi; Bo-Han Zhao; Nan Zhang; Qing-Yue Shen; Li-Ting Hao; Xiang-Yang Wang (Chemical Engineering Journal, 2024)

La promoted Ni0-Niδ+ synergistic interaction for rapid and deep hydrogenation of liquid organic hydrogen carriers - Ting Zhu; Li Liu; Yifang Zhao; Min Gao; Yuan Dong; Dong Xia; Peng Huang; Hansong Cheng; Ming Yang (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Insights into sunlight-driven transformation of tetracycline by iron (hydr)oxides: The dominating role of self-generated hydrogen peroxide - Shiwen Li; Jianming Pang; Wei Han; Ting Chang; Lingen Luo; Xian Li; Jue Liu; Hefa Cheng (Water Research, 2024)

Time-frequency analysis of nonlinear structures under nonstationary excitation by directly solving structural dynamic equation through absolute displacement - Xi-Mei Li; Ting-Long Zhao; Cheng Tao (Soil Dynamics and Earthquake Engineering, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Engineering hyperthermophilic pullulanase to efficiently utilize corn starch for production of maltooligosaccharides and glucose - Ting Xie; Li Zhou.; Laichuang Han; Cuiping You; Zhongmei Liu; Wenjing Cui; Zhongyi Cheng; Junling Guo; Zhemin Zhou (Food Chemistry, 2024)

The improvement of tyrosol bioavailability by encapsulation into liposomes using pH-driven method - Yexuan Yao; Li Ma; Chengwei Yu; Ce Cheng; Hongxia Gao; Teng Wei; Litong Li; Zhiyue Wang; Wei Liu; Zeyuan Deng; Liqiang Zou; Ting Luo (Food Chemistry, 2024)

Incorporating ε-polylysine hydrochloride, tea polyphenols, nisin, and ascorbic acid into edible coating solutions: Effect on oxidation and structure of marinated egg proteins - Jingbo Liu; Lu Han; Dongkun Cheng; Shengrao Li; Xiumei Chen; Yiding Yu; Deju Zhang; Ting Zhang (Food Control, 2024)

A key hub for climate systems: deciphering from Southern Ocean sea surface temperature variability - Ninghong Li; Xufeng Zheng; Ting Su; Xiao Ma; Junying Zhu; Dongdong Cheng (Frontiers in Marine Science, 2024)
The Southern Ocean connects the Pacific, Atlantic, and Indian Oceans, serving as a key hub for the global overturning circulation. The climate of the Southern Ocean is closely linked to the low-latitude equatorial Pacific, as well as the high-latitude regions of the North Atlantic, making it an important component of the global climate system. Due to the interactions of various processes such as atmospheric, oceanic, and ice cover, the Southern Ocean exhibits a complex and variable sea surface temperature structure. Satellite observations indicate that since 1980, the sea surface temperature of the Southern Ocean has been cooling, contrary to the global warming trend. However, due to the relatively short length of satellite observations, the specific mechanisms are not yet clear. Here, we used the EOF method to analyze sea surface temperature data since 1870 (HadISST1 and ERSSTV5), with three main separated modes explaining over 70% of the sea temperature variability. Among them, the first mode shows widespread positive sea surface temperature anomalies in the Southern Ocean, with a time series change consistent with global temperature anomalies, representing a mode of global warming. The second mode corresponds to the Atlantic Multidecadal Oscillation (AMO) but with a lag of approximately 4 years. The third mode is consistent with the variability of the El Niño-Southern Oscillation (ENSO). Furthermore, our study indicates that despite the ongoing global warming since 1980, the negative phase of AMO and positive phase of ENSO may counteract the effects of global warming, leading to an overall cooling trend in the sea surface temperature of the Southern Ocean.

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

CD200R promotes high glucose-induced oxidative stress and damage in human retinal pigment epithelial cells by activating the mTOR signaling pathway - Yaguang Hu; Ting Wei; Shan Gao; Ning Gao; Li Chen; Qiaochu Cheng (Tissue and Cell, 2024)

RATA: A novel class A carbapenemase with broad geographic distribution and potential for global spread - Hongyan Luo; Zhishuang Yang; Ting Lei; Caixia Li; Zuoyong Zhou; Mingshu Wang; Dekang Zhu; Pei Li; Anchun Cheng (Science of The Total Environment, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

The insightful water quality analysis and predictive model establishment via machine learning in dual-source drinking water distribution system - Huiping Li; Baiqin Zhou; Xiaoyan Xu; Ranran Huo; Ting Zhou; Xiaochen Dong; Cheng Ye; Tian Li; Li Xie; Weihai Pang (Environmental Research, 2024)

Low-voltage stimulated denitrification performance of high-salinity wastewater using halotolerant microorganisms - Long Chen; Hai Xiang; Li-Ting Zhou; Yan-Qing Zhang; Yang-Cheng Ding; Di Wu; Nan-Wen Zhu; Yi-Feng Zhang; Hua-Jun Feng (Bioresource Technology, 2024)

Preventive effects of Ramelteon on bleomycin-induced pulmonary fibrosis in mice - Lei Zhang; Ting Cheng; Wenxian Chen; Changsheng Zhong; Mengyang Li; Yilin Xie; Qin Deng; Huifang Wang; Zhenbo Yang; Jin Ju; Haihai Liang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Selective breeding in the noble scallop (Chlamys nobilis) for low-temperature resistance to reduce overwintering losses - Chuanxu Zhang; Cheng He; Yizhou Sun; Hongkuan Zhang; Ting Ye; Faxin Liu; Hongyu Ma; Shengkang Li; Huaiping Zheng (Aquaculture, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

The phytocytokine systemin enhances postharvest tomato fruit resistance to Botrytis cinerea - Pingyu Wang; Ting Wu; Yulin Cheng; Ying Gao; Baowen Huang; Zhengguo Li (Postharvest Biology and Technology, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

Co-hydrothermal carbonization of rape straw and industrial sewage sludge – Applications of hydrochar for N and P adsorptions and for agricultural/horticultural purposes - Chang-Lian Xu; Ailian Li; Xiaoxun Xu; Zhanbiao Yang; Guiyin Wang; Zhang Cheng; Shirong Zhang; Ting Li; Yulin Pu; Guochun Lv; Junzhuo Cai; Wei Zhou; et al. (Journal of Cleaner Production, 2024)

Characterization of the broad-spectrum phage vB_CsaM_CBT2 and its inhibition of multidrug-resistant Cronobacter sakazakii in powered infant formula - Bin Cheng; Diwei Zhang; Ting Wang; Hanfang Chen; Yuhang Wang; Yang Wang; Zongyang Li; Na Ling; Yingwang Ye (Food Control, 2024)

Caspase-8 dependent apoptosis contributes to dyskinesia caused by muscle defects and neurotoxicity in zebrafish exposed to zearalenone - Yunpeng Wang; Shuaiting Li; Zhi Cheng; Ziyuan Zhang; Yu Xu; Huan Zhang; Ting Xu; Jianqiang Chen; Danyang Yin; Wenhua Yan; Huizhe Huang (Food and Chemical Toxicology, 2024)

Efficient bio-remediation of multiple aromatic hydrocarbons using different types of thermotolerant, ring-cleaving dioxygenases derived from Aeribacillus pallidus HB-1 - Mingchang Li; Lu Cao; Dakun Liu; Tianqi Su; Wei Cheng; Guoqiang Li; Ting Ma (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

A hydrogel-based ratiometric fluorescent sensor relying on rhodamine B labelled AIE-featured hyperbranched poly(amido amine) for heparin detection - Cheng Li; Bai-Tong Liu; Yi-Ting Wang; Tian-Jiao Zhang; Xiaochun Zheng; Li Chen; Shaobo Li; Xiaoxian Tian; Dequan Zhang; Yong Wang (Analytica Chimica Acta, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Identification of lncRNA-miRNA-mRNA Networks in the Lenticular Nucleus Region of the Brain Contributes to Hepatolenticular Degeneration Pathogenesis and Therapy - Wenjie Hao; Wenming Yang; Yue Yang; Ting Cheng; Taohua Wei; Lulu Tang; Nannan Qian; Yulong Yang; Xiang Li; Hailin Jiang; Meixia Wang (Molecular Neurobiology, 2024)
Long non-coding RNAs (lncRNAs) are a recently discovered group of non-coding RNAs that play a crucial role in the regulation of various human diseases, especially in the study of nervous system diseases which has garnered significant attention. However, there is limited knowledge on the identification and function of lncRNAs in hepatolenticular degeneration (HLD). The objective of this study was to identify novel lncRNAs and determine their involvement in the networks associated with HLD. We conducted a comprehensive analysis of RNA sequencing (RNA-seq) data, reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and computational biology to identify novel lncRNAs and explore their potential mechanisms in HLD. We identified 212 differently expressed lncRNAs, with 98 upregulated and 114 downregulated. Additionally, 32 differently expressed mRNAs were found, with 15 upregulated and 17 downregulated. We obtained a total of 1131 pairs of co-expressed lncRNAs and mRNAs by Pearson correlation test and prediction and annotation of the lncRNA-targeted miRNA-mRNA network. The differential lncRNAs identified in this study were found to be involved in various biological functions and signaling pathways. These include translational initiation, motor learning, locomotors behavior, dioxygenase activity, integral component of postsynaptic membrane, neuroactive ligand-receptor interaction, nuclear factor-kappa B (NF-κB) signaling pathway, cholinergic synapse, sphingolipid signaling pathway, and Parkinson’s disease signaling pathway, as revealed by the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Six lncRNAs, including XR_001782921.1 ( P < 0.01), XR_ 001780581.1 ( P < 0.01), ENSMUST_00000207119 ( P < 0.01), XR_865512.2 ( P < 0.01), TCONS_00005916 ( P < 0.01), and TCONS_00020683 ( P < 0.01), showed significant differences in expression levels between the model group and normal group by RT-qPCR. Among these, four lncRNAs (TCONS_00020683, XR_865512.2, XR_001780581.1, and ENSMUST00000207119) displayed a high degree of conservation. This study provides a unique perspective for the pathogenesis and therapy of HLD by constructing the lncRNA-miRNA-mRNA network. This insight provides a foundation for future exploration in this field.

Enhanced dewatering extent of sludge by Fe3O4-driven heterogeneous Fenton - Ting Li; Xin Zhang; Yujun Zhou; Jiawei Yang; Fange Cheng; Di Fang; Jianru Liang; Jiansheng Li; Lixiang Zhou (Waste Management, 2024)

Molecular and functional characterization of heat-shock protein 70 in Aphis gossypii under thermal and xenobiotic stresses - Pingzhuo Liang; Mingyu Guo; Dan Wang; Ting Li; Ren Li; Dapeng Li; Shenhang Cheng; Congai Zhen; Lei Zhang (Pesticide Biochemistry and Physiology, 2024)

One-stone, two birds: Three-dimensional structure and rich-inorganic solid electrolyte interface derived from Bi nanoparticles modified Ti3C2/CNT/rGO aerogel for anode-free potassium metal batteries - Dong-Ting Zhang; Mao-Cheng Liu; Min-Peng Li; Zi-Zhou Yuan; Yu-Xia Hu; Hao Chen; Chen-Yang Li; Ling-Bin Kong; Kun Zhao; Jun-Qiang Ren; Bao Liu (Chemical Engineering Journal, 2024)

Epidermal growth factor: Expression in goat endometrial epithelia during early pregnancy and regulation by interferon tau and FOXO1 - Bo Wang; Meng-Die Li; Hai-Yue Xu; Xin-Cheng Zhang; Li-Ge Bu; Ting-Yue Li; Ya Sun; Hua Ni (Animal Reproduction Science, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Key issues to consider toward an efficient constructed wetland-microbial fuel cell: the idea and the reality - Diaodiao Li; Yaqian Zhao; Dan Wei; Cheng Tang; Ting Wei (Environmental Science and Pollution Research, 2024)

Optimization of the adsorption performance of herbal residues as lanthanide ion-modified carriers for phosphate by fly ash and its application - Caigao Zhou; Zihan Chen; Guochun Lv; Changlian Xu; Guiyin Wang; Shirong Zhang; Zhanbiao Yang; Zhang Cheng; Junzhuo Cai; Ting Li; Yulin Pu; Zhien Pu; et al. (Chemosphere, 2024)

Quantitative SARS-CoV-2 exposure assessment for workers in wastewater treatment plants using Monte-Carlo simulation - Cheng Yan; Yi-ning Hu; Zi-cheng Gui; Tian-nuo Lai; Wajid Ali; Nian-hong Wan; Shan-shan He; Sai Liu; Xiang Li; Ting-xu Jin; Zaheer Ahmad Nasir; Sonia Garcia Alcega; et al. (Water Research, 2024)

The adsorption-photocatalytic synergism of LDHs-based nanocomposites on the removal of pollutants in aqueous environment: A critical review - Jing Bai; Xiangling Zhang; Chen Wang; Xuhao Li; Zhouying Xu; Cheng Jing; Ting Zhang; Yinghe Jiang (Journal of Cleaner Production, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Enhancing microbial salt tolerance through low-voltage stimulation for improved p-chloronitrobenzene (p-CNB) removal in high-salinity wastewater - Long Chen; Li-Ting Zhou; Yang-Cheng Ding; Di Wu; Hua-Jun Feng (Science of The Total Environment, 2023)

Characteristics and potential human health risks of microplastics identified in typical clams from South Yellow Sea Mudflat - Qingyuan Guo; Cheng Ding; Zhaoxia Li; Xiao Chen; Jinling Wu; Xuan Li; Jianwei Yu; Chunmiao Wang; Feng Liang; Ting Chen; Bairen Yang; Tianming Chen (Science of The Total Environment, 2023)

Intraspecific variations of leaf hydraulic, economic, and anatomical traits in Cinnamomum camphora along an urban-rural gradient - Cheng Zhang; Nuo Huang; Fengyu Zhang; Ting Wu; Xianjin He; Jianan Wang; Yiyong Li (Science of The Total Environment, 2023)

Screening and genome analysis of lactic acid bacteria with high exopolysaccharide production and good probiotic properties - Jing Lu; Yunren Mao; Ting Ma; Xiaoling Liu; Xiyao Cheng; Yunxia Bai; Shubo Li (Food Bioscience, 2023)

Formation and evolution of a loess sinkhole in the southern Chinese Loess Plateau - Junli Ren; Wei Gong; Cheng Xue; Peng Cheng; Ting Li; Li Ai; Huan Jiang; Xingxing Liu; Yukun Fan; Jianghu Lan; Liangcheng Tan; Youbin Sun (CATENA, 2023)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

In situ growth of polydopamine modified ZIF-L arrays on air-laid paper as flexible evaporator for efficient solar desalination - Long Cheng; Linzhi Zuo; Shitan Yan; Jiubing Shen; Chengping Li; Yiting Che; Liang Wang; Romanov Anton; Ting Bian (Desalination, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

A Novel Large-Scale Three-Dimensional Physical Model Experimental System for Deep Underground Engineering - Xia-Ting Feng; Zheng-Wei Li; Shi-Ming Mei; Jun Tian; Cheng-Xiang Yang; Zhi-Bin Yao; Ji-Kai Gao (Rock Mechanics and Rock Engineering, 2023)

Water source identification in mines combining LIF technology and ResNet - Peng-cheng Yan; Yu-ting Zhao; Guo-dong Li; Jing-bao Wang; Wen-chang Wang (Journal of Mountain Science, 2023)

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Community resilience in city emergency: Exploring the roles of environmental perception, social justice and community attachment in subjective well-being of vulnerable residents - Qian-Cheng Wang; Xuan Liu; Izzy Yi Jian; En-Jia Zhang; Yu-Ting Hou; Kin Wai Michael Siu; Yi-Bin Li (Sustainable Cities and Society, 2023)

Carbon storage capacity of Castanopsis hystrix plantations at different stand–ages in South China - Xu Li; Luis Carlos Ramos Aguila; Jinchu Luo; Yue Liu; Ting Wu; Zhiyang Lie; Xujun Liu; Yan Cheng; Fen Jiang; Juxiu Liu (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Labdane and ent-halimane diterpenoids with STAT3-inhibitory activity from Leonurus sibiricus - Chen Wang; Jiao Tian; Chaoge Liu; Yiming He; Jiahang Li; Qiang Zhang; Ting Xiao; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2023)

Physical informed neural network improving the WRF-CHEM results of air pollution using satellite-based remote sensing data - Bo Li; Qihou Hu; Meng Gao; Ting Liu; Chengxin Zhang; Cheng Liu (Atmospheric Environment, 2023)

Quantifying ant diversity and community in a subalpine forest mosaic: a comparison of two methods - Chuan-Jing Zhang; Yi-Ting Cheng; Xian-Shu Luo; Yao Chen; Yu-Chao He; Yan-Pang Li; Zhi-Pang Huang; Matthew B. Scott; Wen Xiao (Journal of Insect Conservation, 2023)
Sampling efficiency, composition and detection biases associated with pitfall-trap and sample plot (standardised hand-collecting) methods were compared at seven high montane sites at Lasha Mountain, Yunnan, China. Rarefaction-interpolation curves showed total species diversity and sample coverage from each method were undifferentiated. Permutational multivariate analysis of variance showed highly overlapping communities. However, of all species collected, just 53% of all species found were shared between the two methods; 30% were exclusive to sample plot samples and 17% were exclusive to pitfall traps. Modelled comparisons of species richness (alpha) and proportion of species from the population (beta diversity) showed differences between methods. Permutational multivariate analysis of variance blocked by site showed community composition differed between methods, defined largely by the presence of a few dominant species. Implications for insect conservation : Our findings suggest that results from the two methods cannot be directly compared and are imperfect substitutes to one another. For long-term monitoring of biodiversity in complex forest mosaic systems, we suggest integrating a suite of complementary methods to achieve more complete representation of ant composition and diversity.

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

A biomimetic nanoreactor for combinational chemo/chemodynamic therapy of choriocarcinoma through synergistic apoptosis and ferroptosis strategy - Hui Yu; Haoyi Zhao; Yujie Zhang; Yuemin Hou; Runqing Li; Ting Liang; Yuanyuan Zhang; Cheng Li; Jingjie Zhao; Mingzhen Zhang; Ruifang An (Chemical Engineering Journal, 2023)

High-resolution genetic linkage map and height-related QTLs in an oil palm (Elaeis guineensis) family planted across multiple sites - Ngoot-Chin Ting; Pek-Lan Chan; Jaap Buntjer; Jared M. Ordway; Corey Wischmeyer; Leslie Cheng-Li Ooi; Eng Ti Leslie Low; Marhalil Marjuni; Ravigadevi Sambanthamurthi; Rajinder Singh (Physiology and Molecular Biology of Plants, 2023)

The role of exosomes and their enhancement strategies in the treatment of osteoarthritis - Linzhen Huang; Ge Dong; Jie Peng; Ting Li; Mi Zou; Kaibo Hu; Yuan Shu; Tao Cheng; Liang Hao (Human Cell, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Fluorescent noble metal nanoclusters for contaminants analysis in food matrix - Ling Chen; Zehua Cheng; Mai Luo; Ting Wang; Lei Zhang; Jinchao Wei; Yitao Wang; Peng Li (Critical Reviews in Food Science and Nutrition, 2023)

Nitric oxide induces defense responses in apple fruit against black spot disease caused by Alternaria alternata - Jie Han; Yingying Fan; Shicui Li; Binxin Jia; Jin Yang; Aibin Shen; Ting Dai; Jing An; Fengjuan Liu; Cheng Wang (South African Journal of Botany, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Simulation of compound flooding in Japan using a nationwide model - Wei Huang; Yinglong Joseph Zhang; Zhuo Liu; Hao-Cheng Yu; Yi Liu; Sam Lamont; Yu Zhang; Feyera Hirpa; Ting Li; Brett Baker; Wang Zhan; Shabaz Patel; et al. (Natural Hazards, 2023)

Epigenetic Regulation of Ferroptosis in Central Nervous System Diseases - Ting Lan; Ting Ting Sun; Chao Wei; Tian Cheng; Fei Yang; Jian-Nan Zhang; Qian Li (Molecular Neurobiology, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Hyperspectral imaging technique supports dynamic emission inventory of coal-fired power plants in China - Jinan Lin; Chengzhi Xing; Cheng Liu; Wei Tan; Wei Wang; Peng Wu; Chuan Lu; Qihua Li; Ting Liu (Science Bulletin, 2023)

Application of interaction models in predicting the simultaneous growth of Staphylococcus aureus and different concentrations of background microbiota in Chinese-style braised beef - Chuansong Cheng; Binxiong Liu; Meiling Tian; Ting Fang; Changcheng Li (Meat Science, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Characterization of ionic liquids removing heavy metals from electroplating sludge: Influencing factors, optimisation strategies and reaction mechanisms - Chenchen Cao; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Yulin Pu; Guochun Lv; Changlian Xu; Junzhuo Cai; Wei Zhou; et al. (Chemosphere, 2023)

Boosting piezo-photocatalytic activity of BiVO4/BiFeO3 heterojunctions through built-in polarization field tailoring carrier transfer performances - Qinfang Jing; Zhiyong Liu; Xian Cheng; Cichun Li; Pengrong Ren; Kun Guo; Haojie Yue; Bing Xie; Ting Li; Zhiguo Wang; Longlong Shu (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A review on fabricating functional materials by electroplating sludge: process characteristics and outlook - Chenchen Cao; Jian Yu; Xiaoxun Xu; Feng Li; Zhanbiao Yang; Guiyin Wang; Shirong Zhang; Zhang Cheng; Ting Li; Yulin Pu; Junren Xian; Yuanxiang Yang; et al. (Environmental Science and Pollution Research, 2023)

Regulating the concentration of dissolved oxygen to achieve the directional transformation of reactive oxygen species: A controllable oxidation process for ciprofloxacin degradation by calcined CuCoFe-LDH - Shaohong Wang; Ting Li; Xiang Cheng; Runliang Zhu; Yin Xu (Water Research, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Application and mechanism analysis of functionalized ionic liquids in copper regeneration from electroplating sludge - Feng Li; Xiaoxun Xu; Chenchen Cao; Zhanbiao Yang; Guiyin Wang; Ting Li; Yulin Pu; Shirong Zhang; Zhang Cheng; Guochun Lv; Changlian Xu; Junren Xian; et al. (Journal of Cleaner Production, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Comprehensive treatment strategy for diesel truck exhaust - Tian Li; Hai-Li Yang; Le-Tian Xu; Yu-Ting Zhou; Yong-Jun Min; Shi-Cheng Yan; Yong-Hui Zhang; Xiao-Ming Wang (Environmental Science and Pollution Research, 2023)

Identification of a new benzophenanthridine alkaloid from Eomecon chionantha induced necroptosis in breast cancer cells - Peng Yang; Ya-ting Cheng; Xin Huang; Bin Huang; Li Yi; Hai-lang He; Yang Xie (Natural Product Research, 2023)

Edwardsiella piscicida Ail1: An outer membrane protein required for host infection - Mo-fei Li; Yu-ting Du; Cheng-dong Jin; Xue-peng Li; Yuan-yuan Sun (Aquaculture, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

Unusual uranium biomineralization induced by green algae: Behavior investigation and mechanism probe - Yanxia Cheng; Ting Zhang; Shunzhang Chen; Feize Li; Renwei Qing; Tu Lan; Yuanyou Yang; Jiali Liao; Ning Liu (Journal of Environmental Sciences, 2023)

Using transcriptomics to reveal the molecular mechanism of higher alcohol metabolism in Saccharomyces cerevisiae - Danyao Cui; Ling Liu; Xiaoyuan Zhang; Liangcai Lin; Xin Li; Ting Cheng; Chunhui Wei; Yu Zhang; Zheng Zhou; Wei Li; Cuiying Zhang (Food Bioscience, 2023)

Efficient electromagnetic wave absorption performances dominated by exchanged resonance of lightweight PC/Fe3O4@PDA hybrid nanocomposite - Yuxin Xie; Yuying Guo; Tingting Cheng; Laibin Zhao; Ting Wang; Alan Meng; Meng Zhang; Zhenjiang Li (Chemical Engineering Journal, 2023)

A topical platelet-independent multilevel clotting initiator for intraoperative hemostasis - Fenglin Miao; Huirong Lin; Tianhong Yao; Ruyi Zhang; Xinfei Sun; Hongwei Cheng; Lingwei Gu; Xiaogang Xia; Ting Wu; Wengang Li; Gang Liu (Chemical Engineering Journal, 2023)

Optimizing the Schoenemann Reaction for Colorimetric Assays of VX and GD - Shaoxiong Wu; Lianyuan Wang; Haiyan Zhu; Ling Yuan; Jian Li; Liang Ge; Hongpeng Zhang; Ting Miao; Zhenxing Cheng (Bulletin of Environmental Contamination and Toxicology, 2023)

Recyclable magnetic Fe3O4@C for methylene blue removal under microwave-induced reaction system - Wen-Wen Li; Long Cheng; Jing Liu; Shi-Yong Yang; Shu-Ting Zan; Guang-Chao Zhao (Chemosphere, 2023)

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Atmospheric environment monitoring technology and equipment in China: A review and outlook - Youwen Sun; Ting Yang; Huaqiao Gui; Xin Li; Weigang Wang; Jun Duan; Shushuai Mao; Hao Yin; Bin Zhou; Jianlei Lang; Haijin Zhou; Cheng Liu; et al. (Journal of Environmental Sciences, 2023)

The optimum cooking time: A possible key index for predicting the deterioration of fresh white-salted noodle - Qin Guo; Yun-ting Li; Jia-hui Cai; Cheng-wan Ren; Muhammad Adil Farooq; Bin Xu (Journal of Cereal Science, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Rational design of ZnO-based aqueous batteries for safe, fast, and reliable energy storage: Accomplishment of stable K+ storage/release - Ting Liu; Shuang Cheng; Luping Li; Xu Ji; Gyutae Nam; Xingbin Yan; Meilin Liu (Chemical Engineering Journal, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China - Weize Xu; Die Li; Zehua Shao; Yanqin You; Feixia Pan; Hongliang Lou; Jing Li; Yueqin Jin; Ting Wu; Lulu Pan; Jing An; Junqiu Xu; et al. (Environmental Science and Pollution Research, 2022)

Insight into the evolution characteristics on molecular weight of compost dissolved organic matters using high-performance size exclusion chromatography combined with a two-dimensional correlation analysis - Xufang Yu; Ao Cheng; Dan Chen; Ting Li; Xingjun Fan; Xiang Wang; Wenchao Ji; Jianfei Wang; Lantian Ren (Environmental Science and Pollution Research, 2022)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

COLREGS-Complied Automatic Collision Avoidance for the Encounter Situations of Multiple Vessels - Ting Sun; Cheng Liu; Shuang Xu; Qizhi Hu; Cheng Li (Journal of Marine Science and Engineering, 2022)
In crowded waters, the incidence of collision accidents of multiple vessels has increased significantly, most of which can be ascribed to human factors, particularly, human decision-making failures and inobservance with International Regulations for Preventing Collisions at Sea (COLREGS). On this basis, an automatic collision avoidance strategy for the encounter situations of multiple vessels is proposed herein. First of all, a COLREGS-complied evasive action decision-making mechanism is established, which can determine the evasive action from the give-way vessel and stand-on vessel separately. It is worth emphasizing that the situation of vessels against COLREGS is taken into consideration herein. Furthermore, a novel automatic collision avoidance controller of multiple vessels on account of model predictive control (MPC) is devised, which can carry out control action ahead of time and handle the problem of rudder saturation. Finally, the effectiveness of the proposed automatic collision avoidance strategy of multiple vessels is illustrated via extensive simulations.

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Correction to: Source apportionment and health risk assessment of air pollution particles in eastern district of Chengdu - Yi Huang; Li Wang; Shipeng Zhang; Meng Zhang; Jinjin Wang; Xin Cheng; Ting Li; Min He; Shijun Ni (Environmental Geochemistry and Health, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Two novel and efficient plant composites for the degradation of oxytetracycline: nanoscale ferrous sulphide supported on rape straw waste - Yan Yang; Xiaoxun Xu; Shirong Zhang; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Junren Xian; Ting Li; Yulin Pu; Wei Zhou; Gang Xiang (Environmental Science and Pollution Research, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Investigation and experimental validation of curcumin-related mechanisms against hepatocellular carcinoma based on network pharmacology - Yang Chen; Qian Li; Sisi Ren; Ting Chen; Bingtao Zhai; Jiangxue Cheng; Xiaoyan Shi; Liang Song; Yu Fan; Dongyan Guo (Journal of Zhejiang University-SCIENCE B, 2022)

The effect of meteorological drought on vegetation cover in the Yellow River basin, China - Lu Jia; Kun‐xia Yu; Zhan‐bin Li; Peng Li; Guo‐ce Xu; Yu‐ting Cheng; Xiang Zhang; Zhi Yang (International Journal of Climatology, 2022)
As a widespread natural disaster, drought has a significant impact on changes in regional vegetation cover. Based on 1‐month standardized precipitation index (SPI1), this study took the Yellow River basin (YRB) with frequent droughts as the research object, using NDVI data from 1999 to 2018, Mann–Kendall trend test, and correlation test to study the temporal and spatial characteristics of meteorological drought, explored the response of vegetation cover to meteorological drought, and further discussed the possible factors affecting meteorological drought. The results of the study showed that from 1999 to 2018, the SPI1 in the YRB had not increased significantly in a large area in different months ( p > .05). On the monthly time scale, the NDVI of the YRB gradually increased from north to south, showing a significant increasing trend the central area ( p p p

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Abnormal functional connectivity of the salience network in insomnia - Yongxin Cheng; Ting Xue; Fang Dong; Yiting Hu; Mi Zhou; Xiaojian Li; Ruoyan Huang; Xiaoqi Lu; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2022)

Unexpected role of electron‐transfer hub in direct degradation of pollutants by exoelectrogenic bacteria - Ting‐Ting Zhu; Zhou‐Hua Cheng; Sheng‐Song Yu; Wen‐Wei Li; Dong‐Feng Liu; Han‐Qing Yu (Environmental Microbiology, 2022)
Summary Exoelectrogenic bacteria (EEB) are capable of anaerobic respiration with diverse extracellular electron acceptors including insoluble minerals, electrodes and flavins, but the detailed electron transfer pathways and reaction mechanisms remain elusive. Here, we discover that CymA, which is usually considered to solely serve as an inner‐membrane electron transfer hub in Shewanella oneidensis MR‐1 (a model EEB), might also function as a reductase for direct reducing diverse nitroaromatic compounds (e.g. 2,4‐dichloronitrobenzene) and azo dyes. Such a process can be accelerated by dosing anthraquinone‐2,6‐disulfonate. The CymA‐based reduction pathways in S . oneidensis MR‐1 for different contaminants could be functionally reconstructed and strengthened in Escherichia coli . The direct reduction of lowly polar contaminants by quinol oxidases like CymA homologues might be universal in diverse microbes. This work offers new insights into the pollutant reduction mechanisms of EEB and unveils a new function of CymA to act as a terminal reductase.

Optimizing Fertilizer Management Based on Controlled-Release Fertilizer to Improve Yield, Quality, and Reduce Fertilizer Application on Apples - Junyin Li; Yan Liu; Yafu Tang; Junfei Shao; Ting Xu; Ronghui Ma; Yuanmao Jiang; Dongdong Cheng (Journal of Soil Science and Plant Nutrition, 2022)

Prevalence and molecular epidemiology of equine piroplasmosis in China: a neglected tick-borne disease - Kewei Chen; Zhe Hu; Jingkun Li; Jingfei Wang; Diqiu Liu; Ting Qi; Wei Guo; Cheng Du; Xiaojun Wang (Science China Life Sciences, 2022)

A Hydroponic Study on Effect of Zinc Against Mercury Uptake by Triticale: Kinetic Process and Accumulation - Ting Liu; Yi Man; Ping Li; Hua Zhang; Huangxin Cheng (Bulletin of Environmental Contamination and Toxicology, 2022)

Spatio-temporal characteristics of population and economy in transitional geographic space at the southern end of “Hu Huan-yong Line” - Wei Deng; Yu-fang Cheng; Huan Yu; Li Peng; Bo Kong; Yu-ting Hou (Journal of Mountain Science, 2022)

Spatial analyses of factors affecting household structure in Chinese cities: The case of three-generation lineal households - Ting Li; Tao Liu; Jiajie Liu; Tianyi Cheng (Journal of Geographical Sciences, 2022)

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

A genetic platform for predicting and reducing non-tenera contamination in oil palm (Elaeis guineensis) seed supply - Rajinder Singh; Leslie Cheng-Li Ooi; Ngoot-Chin Ting; Eng-Ti Leslie Low; Meilina Ong-Abdullah; Rajanaidu Nookiah; Marhalil Marjuni; Suzana Mustaffa; Mohamad Arif Abdul Manaf; Peggy Garner; Jerry Reed; Corey Wischmeyer; et al. (Tree Genetics & Genomes, 2021)

Experimental Investigation on the Mechanism of Coal and Gas Outburst: Novel Insights on the Formation and Development of Coal Spallation - Yang Lei; Yuanping Cheng; Ting Ren; Qingyi Tu; Yixuan Li; Longyong Shu (Rock Mechanics and Rock Engineering, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Quantitative microbial risk assessment for occupational health of temporary entrants and staffs equipped with various grade PPE and exposed to microbial bioaerosols in two WWTPs - Cheng Yan; Ya-li Leng; Jun-ting Wu (International Archives of Occupational and Environmental Health, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Impact of the April–May SAM on Central Pacific Ocean sea temperature over the following three seasons - Ting Liu; Jianping Li; Cheng Sun; Tao Lian; Yazhou Zhang (Climate Dynamics, 2021)
Although the impact of the extratropical Pacific signal on the El Niño–Southern Oscillation has attracted increasing concern, the impact of Southern Hemisphere Annular Mode (SAM)-related signals from outside the southern Pacific Basin on the equatorial sea temperature has received less attention. This study explores the lead correlation between the April–May (AM) SAM and central tropical Pacific sea temperature variability over the following three seasons. For the positive AM SAM case, the related simultaneous warm SST anomalies in the southeastern Indian Ocean favor significant regulation of vertical circulation in the Indian Ocean with anomalous ascending motion in the tropics. This can further enhance convection over the Marine Continent, which induces a significant horizontal Kelvin response and regulates the vertical Walker circulation. These two processes both result in the anomalous easterlies east of 130° E in the equatorial Pacific during AM. These easterly anomalies favor oceanic upwelling and eastward propagation of the cold water into the central Pacific. The cold water in turn amplifies the development of the easterly wind and further maintains the cold water into the boreal winter. The results presented here not only provide a possible link between extratropical climate variability in the Indian Ocean and climate variation in the equatorial Pacific, but also shed new light on the short-term prediction of tropical central Pacific sea temperature.

Exploring the validity of using immersive virtual reality technique on perceived crowding of recreational environment - Ting-Hsuan Wang; Wan-Hsuan Wu; Li Shen; Chia-Kuen Cheng (Landscape and Ecological Engineering, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Investigation of brain damage mechanism in middle cerebral artery occlusion/reperfusion rats based on i-TRAQ quantitative proteomics - Quantao Ma; Chunguo Wang; Min Wang; Yaqi Li; Pengfei Li; Jingkang Wang; Long Cheng; Yongcheng An; Hongyu Dai; Yuhui Duan; Ting Wang; Baosheng Zhao (Experimental Brain Research, 2021)

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

The Energy Principle of Coal and Gas Outbursts: Experimentally Evaluating the Role of Gas Desorption - Yang Lei; Yuanping Cheng; Ting Ren; Qingyi Tu; Longyong Shu; Yixuan Li (Rock Mechanics and Rock Engineering, 2021)

High bioremediation potential of strain Chenggangzhangella methanolivorans CHL1 for soil polluted with metsulfuron-methyl or tribenuron-methyl in a pot experiment - Ting-Ting Yang; Hui-Wen Zhang; Jian Wang; Xin-Yu Li; Xu Li; Zhen-Cheng Su (Environmental Science and Pollution Research, 2021)

Strategic interactions in environmental regulation enforcement: evidence from Chinese cities - Kangkang Zhang; Deyi Xu; Shiran Li; Ting Wu; Jinhua Cheng (Environmental Science and Pollution Research, 2021)

Improving the Diagnostic Ability of the Sleep Apnea Screening System Based on Oximetry by Using Physical Activity Data - Cheng-Han Wu; Jui-Hsuan Lee; Terry B. J. Kuo; Chun-Ting Lai; Lieber P. H. Li; Cheryl C. H. Yang (Journal of Medical and Biological Engineering, 2020)

WDR5a functions in cadmium-inhibited root meristem growth by regulating nitric oxide accumulation in Arabidopsis - Yu Zhang; Yang-Yang Tian; Lin-Feng Wang; Yun-Hui Li; Ting-Ting Li; Wen-Cheng Liu (Planta, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

2(5H)-Furanone Disrupts Bacterial Biofilm Formation and Indirectly Reduces the Settlement of Plantigrades of the Mussel Mytilus coruscus - Yi-Feng Li; Xin Zhu; Zhi-Yang Cheng; Xiao Liang; You-Ting Zhu; Dan-Dan Feng; Sergey Dobretsov; Jin-Long Yang (Frontiers in Marine Science, 2020)

Annual Characteristics, Source Analysis of PM1-Bound Potentially Harmful Elements in the Eastern District of Chengdu, China - Jinjin Wang; Yi Huang; Ting Li; Huibin Shi; Min He; Xin Cheng; Shijun Ni; Chengjiang Zhang (Archives of Environmental Contamination and Toxicology, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

Source apportionment and health risk assessment of air pollution particles in eastern district of Chengdu - Yi Huang; Li Wang; Shipeng Zhang; Meng Zhang; Jinjin Wang; Xin Cheng; Ting Li; Min He; Shijun Ni (Environmental Geochemistry and Health, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Transcriptome analysis revealed cadmium accumulation mechanisms in hyperaccumulator Siegesbeckia orientalis L. - Xiaoxun Xu; Shirong Zhang; Zhang Cheng; Ting Li; Yongxia Jia; Guiyin Wang; Zhanbiao Yang; Junren Xian; Yuanxiang Yang; Wei Zhou (Environmental Science and Pollution Research, 2020)

Dynamic change of vegetation and its response to climate and topographic factors in the Xijiang River basin, China - Lu Jia; Zhan-bin Li; Guo-ce Xu; Zong-ping Ren; Peng Li; Yu-ting Cheng; Yi-xin Zhang; Bin Wang; Jia-xin Zhang; Shu Yu (Environmental Science and Pollution Research, 2020)

Phenotypic, genetic, and molecular function of msc-2, a genic male sterile mutant in pepper (Capsicum annuum L.) - Qing Cheng; Ting Li; Yixin Ai; Qiaohua Lu; Yihao Wang; Lang Wu; Jinqiu Liu; Liang Sun; Huolin Shen (Theoretical and Applied Genetics, 2020)

Fine Mapping of the High-pH Tolerance and Growth Trait-Related Quantitative Trait Loci (QTLs) and Identification of the Candidate Genes in Pacific White Shrimp (Litopenaeus vannamei) - Wen Huang; Chuhang Cheng; Jinshang Liu; Xin Zhang; Chunhua Ren; Xiao Jiang; Ting Chen; Kaimin Cheng; Huo Li; Chaoqun Hu (Marine Biotechnology, 2020)

Characterization of a New Isolate of Chilli ringspot virus in Yunnan, China - Md. Siddiqur Rahman; Xiaoxia Su; Kuanyu Zheng; Xiaofei Cheng; Ting Li; Lihua Zhao; Jiahong Dong; Zhongkai Zhang (Journal of Crop Science and Biotechnology, 2020)

Metabolomics and physiological analyses reveal β-sitosterol as an important plant growth regulator inducing tolerance to water stress in white clover - Zhou Li; Bizhen Cheng; Bin Yong; Ting Liu; Yan Peng; Xinquan Zhang; Xiao Ma; Linkai Huang; Wei Liu; Gang Nie (Planta, 2019)

The relationship among probabilistic, deterministic and potential skills in predicting the ENSO for the past 161 years - Ting Liu; Youmin Tang; Dejian Yang; Yanjie Cheng; Xunshu Song; Zhaolu Hou; Zheqi Shen; Yanqiu Gao; Yanling Wu; Xiaojing Li; Banglin Zhang (Climate Dynamics, 2019)
Here, we explored in depth the relationship among the deterministic prediction skill, the probabilistic prediction skill and the potential predictability. This was achieved by theoretical analyses and, in particular, by an analysis of long-term ensemble ENSO hindcast over 161 years from 1856 to 2016. First, a nonlinear monotonic relationship between the deterministic prediction skill and the probabilistic prediction skill, derived by theoretical analysis, was examined and validated using the ensemble hindcast. Further, the co-variability between the potential predictability and the deterministic prediction skill was explored in both perfect model assumption and actual model scenario. On these bases, we investigated the relationship between the potential predictability and probabilistic prediction skill from both the practice of ENSO forecast and theoretical perspective. The results of the study indicate that there are nonlinear monotonic relationships among these three kinds of measures. The potential predictability is considered to be a good indicator for the actual prediction skill in terms of both the deterministic measures and the probabilistic framework. The relationships identified here exhibit considerable significant practical sense to conduct predictability researches, which provide an inexpensive and moderate approach for inquiring prediction uncertainties without the requirement of costly ensemble experiments.

Fusarium oxysporum KB-3 from Bletilla striata: an orchid mycorrhizal fungus - Jianwei Jiang; Ke Zhang; Sheng Cheng; Qianwen Nie; Shen-xian Zhou; Qingqing Chen; Jinglong Zhou; Xiao Zhen; Xue ting Li; Tong wen Zhen; Mingyue Xu; Tom Hsiang; et al. (Mycorrhiza, 2019)

Experimental Study to Design an Analog Material for Jinping Marble with High Strength, High Brittleness and High Unit Weight and Ductility - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Cheng-Xiang Yang; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2019)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Brick tea consumption is a risk factor for dental caries and dental fluorosis among 12-year-old Tibetan children in Ganzi - Rui Zhang; Li Cheng; Tao Zhang; Ting Xu; Meng Li; Wei Yin; Qingling Jiang; Yingming Yang; Tao Hu (Environmental Geochemistry and Health, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

In Situ Observation of Rock Spalling in the Deep Tunnels of the China Jinping Underground Laboratory (2400 m Depth) - Xia-Ting Feng; Hong Xu; Shi-Li Qiu; Shao-Jun Li; Cheng-Xiang Yang; Hao-Sen Guo; Yuan Cheng; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2018)

In Situ Observation of Hard Surrounding Rock Displacement at 2400-m-Deep Tunnels - Xia-Ting Feng; Zhi-Bin Yao; Shao-Jun Li; Shi-Yong Wu; Cheng-Xiang Yang; Hao-Sen Guo; Shan Zhong (Rock Mechanics and Rock Engineering, 2018)

Exclosure on CT-measured soil macropore characteristics in the Inner Mongolia grassland of northern China - Xia Hu; Yan-Li Lyu; Yong Liu; Xiao-Yan Li; Zhen-Ting Sun; Zong-Chao Li; Ya-Qian Cheng; Lan-Lan Guo; Lian-You Liu (Journal of Soils and Sediments, 2018)

Terpenoids from Vitex trifolia and their anti-inflammatory activities - Fengyan Bao; Ruotian Tang; Li Cheng; Cuiyun Zhang; Chongyue Qiu; Ting Yuan; Lihan Zhu; Hua Li; Lixia Chen (Journal of Natural Medicines, 2018)

In vitro and In vivo Studies on a Novel Bioadhesive Colloidal System: Cationic Liposomes of Ibuprofen - Xiumei Gai; Lizhen Cheng; Ting Li; Dandan Liu; Yanyan Wang; Tuanjie Wang; Weisan Pan; Xinggang Yang (AAPS PharmSciTech, 2018)

Epigenetic modification of TLE1 induce abnormal differentiation in diabetic mice intestinal epithelium - Ji-hao Xu; Guang-cheng Chen; Can-ze Huang; Di Cheng; Ting-feng Wu; Si-yi Wang; Jie-yao Li; Tao Yu; Qi-kui Chen (Molecular and Cellular Biochemistry, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

Application of Adipose-Derived Stem Cells to Observe the Morphological Changes by Induction with Decellularized Corneal Extracellular Matrix and Specified Medium - Hsu-Wei Fang; Li-Ting Li; Shou-Cheng Teng; Tsung-Jen Wang (Journal of Medical and Biological Engineering, 2017)

Seasonal and inter-annual variations of Arctic cyclones and their linkage with Arctic sea ice and atmospheric teleconnections - Lixin Wei; Ting Qin; Cheng Li (Acta Oceanologica Sinica, 2017)

Deletion of TpKu70 facilitates gene targeting in Talaromyces pinophilus and identification of TpAmyR involvement in amylase production - Ting Zhang; Shuai Zhao; Lu-Sheng Liao; Cheng-Xi Li; Gui-Yan Liao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2017)

The implication of salience network abnormalities in young male adult smokers - Yangding Li; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yanzhi Bi; Sha Shi; Ting Xue; Xiaoqi Lu; Wei Qin; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Evaluation of the Integrity of Deep Rock Masses Using Results of Digital Borehole Televiewers - Hao-Sen Guo; Xia-Ting Feng; Shao-Jun Li; Cheng-Xiang Yang; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Protective effects of vitamins C and E on dichlorodiphenyltrichloroethane-induced genotoxicity and hepatotoxicity in human liver cells - Xiao Ting Jin; Li Song; Xiang Yuan Liu; Hang Qing Li; Long Cheng; Zhuo Yu Li (Molecular & Cellular Toxicology, 2017)

Identification and characterization of multiple porcine astrovirus genotypes in Hunan province, China - Chao-Ting Xiao; Zhang Luo; Sun-Liang Lv; Tanja Opriessnig; Run-Cheng Li; Xing-Long Yu (Archives of Virology, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Purified isolation of vacuoles from Sedum alfredii leaf-derived protoplasts - Xiao-yu Gao; Xing-cheng Liao; Ruo-lai Wu; Ting Liu; Hai-xing Wang; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Influence of genetic polymorphisms in cytochrome P450 oxidoreductase on the variability in stable warfarin maintenance dose in Han Chinese - Wu-Tao Zeng; Qing Xu; Cheng-Hsun Li; Wei-Yan Chen; Xiu-Ting Sun; Xiang Wang; Yi-Ying Yang; Hui Shi; Zhi-Sheng Yang (European Journal of Clinical Pharmacology, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Fine mapping of the dialytic gene that controls multicellular trichome formation and stamen development in tomato - Jiang Chang; Ting Yu; Shenghua Gao; Cheng Xiong; Qingmin Xie; Hanxia Li; Zhibiao Ye; Changxian Yang (Theoretical and Applied Genetics, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Evaluating the fraction of electrically associated cations on surfaces of soil particles by extrapolation of strong-field Wien effect measurements in dilute suspensions - Ting-Ting Fan; Yu-Jun Wang; Cheng-Bao Li; Juan Gao; Dong-Mei Zhou; Shmulik P. Friedman (Journal of Soils and Sediments, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Analysis of EDZ Development of Columnar Jointed Rock Mass in the Baihetan Diversion Tunnel - Xian-Jie Hao; Xia-Ting Feng; Cheng-Xiang Yang; Quan Jiang; Shao-Jun Li (Rock Mechanics and Rock Engineering, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

A theoretical analysis of the bearing performance of vertically loaded large-diameter pipe pile groups - Xuanming Ding; Ting Zhang; Ping Li; Ke Cheng (Journal of Ocean University of China, 2016)

Levels and ecological risk assessment of metals in soils from a typical e-waste recycling region in southeast China - Weituo Zhao; Lei Ding; Xiaowen Gu; Jie Luo; Yunlang Liu; Li Guo; Yi Shi; Ting Huang; Shenggao Cheng (Ecotoxicology, 2015)

Functional variant in methionine synthase reductase intron-1 is associated with pleiotropic congenital malformations - Haiqin Cheng; Huili Li; Zhaoli Bu; Qin Zhang; Baoling Bai; Hong Zhao; Ren-Ke Li; Ting Zhang; Jun Xie (Molecular and Cellular Biochemistry, 2015)

Variation of levels and distribution of N-nitrosamines in different seasons in drinking waters of East China - Ting Li; Dian Yu; Qiming Xian; Aimin Li; Cheng Sun (Environmental Science and Pollution Research, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Forest canopy height mapping over China using GLAS and MODIS data - Ting Yang; Cheng Wang; GuiCai Li; SheZhou Luo; XiaoHuan Xi; Shuai Gao; HongCheng Zeng (Science China Earth Sciences, 2015)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

The complete S RNA and M RNA nucleotide sequences of a hippeastrum chlorotic ringspot virus (HCRV) isolate from Hymenocallis littoralis (Jacq.) Salisb in China - Ye Xu; Shi-gao Lou; Xiao-lin Li; Yuan-xian Zheng; Wen-cheng Wang; Ya-ting Liu (Archives of Virology, 2013)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

The influences of weir construction on salt water intrusion and water quality in a tidal estuary—assessment with modeling study - Wei-Bo Chen; Wen-Cheng Liu; Li-Ting Huang (Environmental Monitoring and Assessment, 2013)

Simultaneous removal of cadmium and sulfamethoxazole from aqueous solution by rice straw biochar - Xuan Han; Cheng-feng Liang; Ting-qiang Li; Kai Wang; Hua-gang Huang; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Differential autophagic cell death under stress with ectopic cytoplasmic and mitochondrial-specific PPP2R2B in human neuroblastoma cells - Kang Fang; Hui-Fang Li; Chang-Heng Hsieh; Dan-Yu Li; Ding-Chieh Song; Wan-Ting Cheng; Zhi-Xuan Guo (Apoptosis, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Characteristics and evolution of the PUF gene family in Bombyx mori and 27 other species - Chun-Dong Zhang; Min-Hui Pan; Juan Tan; Fang-Fang Li; Jun Zhang; Ting-Ting Wang; Cheng Lu (Molecular Biology Reports, 2012)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

Isolation of a new monoterpenic ester from the leaves of Michelia compressa (Maxim.) Sargent var. formosana Kanehira (Magnoliaceae) - Ming-Jen Cheng; Wen-Li Lo; Jin-Cherng Huang; Yu-Ting Yeh; Zi-Ling Hong; Yu-Cheng Lu; Ming-Sung Chang; Chung-Yi Chen (Natural Product Research, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Regulation of ATGL expression mediated by leptin in vitro in porcine adipocyte lipolysis - Yu-cheng Li; Xue-li Zheng; Bing-ting Liu; Gong-she Yang (Molecular and Cellular Biochemistry, 2010)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Synthesis, Crystal, Absorption and Fluorescence Spectroscopy of Nitro-Stilbene Derivatives with Benzophenones - Fang Gao; Ting Xie; Zhibin Cheng; Nvdan Hu; Long Yang; Yun Gong; Shengtao Zhang; Hongru Li (Journal of Fluorescence, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A Climatology Model for Forecasting Typhoon Rainfall in Taiwan - Cheng-Shang Lee; Li-Rung Huang; Horng-Syi Shen; Shi-Ting Wang (Natural Hazards, 2006)

Eudragit E Accelerated the Diketopiperazine Formation of Enalapril Maleate Determined by Thermal FTIR Microspectroscopic Technique - Shun-Li Wang; Shan-Yang Lin; Ting-Fang Chen; Wen-Ting Cheng (Pharmaceutical Research, 2004)

The application of very high resolution satellite image in urban vegetation cover investigation: A case study of Xiamen City - Cheng Chengqi; Li Bin; Ma Ting (Journal of Geographical Sciences, 2003)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)